Is a Cephalomedullary Nail Durable Treatment for Patients With Metastatic Peritrochanteric Disease?. Issue 12 (December 2018) - Chafey, David H.; Lewis, Valerae O.; Satcher, Robert L.; Moon, Bryan S.; Lin, Patrick P.
Abstract: Background: Although cephalomedullary nail fixation is often used for metastatic peritrochanteric lesions of the femur, there is concern regarding the durability of the implant in comparison to endoprosthetic reconstruction. Previous studies have reported the proportion of patients who undergo reoperation for loss of stability, but the adequacy of the construct has not been critically evaluated in a competing risk analysis that incorporates death of the patient in the calculation. Questions/purposes: (1) What is the cumulative incidence of reoperation of cephalomedullary nails with death as a competing risk for metastatic lesions of the proximal femur? (2) What is the survival of patients with metastases to the proximal femur after cephalomedullary nailing? (3) What clinical factors are associated with implant stability in these patients? Methods: Between 1990 and 2009, 11 surgeons at one center treated 217 patients with cephalomedullary nails for metastatic proximal femoral lesions. This represented 40% (217 of 544) of the patients undergoing surgery for metastases in this location during the study period. In general, we used cephalomedullary nails when there was normal bone in the femoral head, no fracture in the neck, and a moderate-sized lesion; we favored bipolar hemiarthroplasty for femoral neck fractures and disease affecting the femoral head; finally, we used proximal femoral endoprosthetic replacement for large lesions with severe bone destruction. A retrospective study was conducted of 199 patients with cephalomedullary nails for peritrochanteric metastases from 1990 to 2009. Pathologic fracture, defined as a breach in cortex with a clear fracture line either with or without displacement, was present in 61 patients. The most common primary cancers were breast (42 of 199 patients [21%]), lung (37 of 199 patients [18%]), and renal cell (34 of 199 patients [17%]). A competing risk analysis was performed to describe the cumulative incidence of implant revision. Patient overall survival was assessed by Kaplan-Meier survivorship. A univariate analysis was performed to determine whether there was an association between revision surgery and various patient factors, including tumor histology, pathologic fracture, cementation, and radiation. Results: Loss of implant stability necessitating revision surgery occurred in 19 of 199 patients (10%). In a competing risk analysis with death of the patient as the competing event, the cumulative incidence of revision surgery was 5% (95% confidence interval [CI], 3%-9%) at 12 months and 9% (95% CI, 5%-13%) at 5 years. Using Kaplan-Meier analysis, the overall patient survival was 31% (95% CI, 25%-37%) at 12 months and 5% (95% CI, 3%-9%) at 60 months. Patients with lung cancer had the shortest overall survival of 11% (95% CI, 1%-21%) at 12 months, and patients with multiple myeloma had the longest overall survival of 71% (95% CI, 49%-94%) at 12 months (p < 0.001). Duration of patient survival beyond the median 7 months was the only factor associated with a greater likelihood of revision surgery. Factors not associated with revision included tumor histology, pathologic fracture, closed versus open nailing, cementation, gender, age, and postoperative radiation. Conclusions: The competing risk analysis demonstrates a relatively low cumulative incidence of reoperation and suggests that cephalomedullary nailing is reasonable for patients with moderate-sized proximal femoral metastasis not affecting the femoral head. For the large majority of patients, the construct achieves the goal of stabilizing the femur for the duration of the patient's life. Longer patient survival was associated with greater risk of revision surgery, but no particular tumor histology was found to have a greater cumulative incidence of reoperation. Future work with a larger number of patients and stricter surgical indications may be needed to corroborate these findings. Level of Evidence: Level III, therapeutic study.